3(2x+1)=2(x+1)+1
Step 1:Simplify both sides of the equation
(3)(2x)+(3)(1)=(2)(x)+(2)(1)+ -(distribute)
6x+3=2x+2+1
6x+3=(2x)+(2+1) -(Combine Like Terms)
6x+3=2x+3
Step 2: Subtract 2x from both sides
6x+3-2x=2x+3-2x
4x+3-3=3-3
4x÷4=0÷4
x=0
3x - 4y = 9
-3x + 2y = 9
Answer:
[-9, -9]
Step-by-step explanation:
Here is how the Eliminasyon Metòd is done:
{3x- 4y = 9
{-3x+ 2y = 9
--------------
-2y = 18; -9 = y [plug this back into both equations for y to get -9 = x]
If you are ever in need of assistance, do not hesitate to let me know by subscribing to my You-Tube channel [USERNAME: MATHEMATICS WIZARD], and as always, I am joyous to assist anyone at any time.
**I do have videos that talk about how to solve systems of equations in two to three variables using the Elimination and Substitution methods. I encourage you to check them out!
Answer:
Step-by-step explanation:
Start by getting rid of the addition sign, as a positive multiplied by a negative is negative:
Subtract from both sides of the equation:
Divide both sides of the equation by the coefficient of , which is :
or
_
Check your by substituting the solved value in to the initial equation:
Since both sides of the equation are equal, our answer is correct!
Answer:
q=-2
Step-by-step explanation: